Navigating the Paradox of Green Technology Adoption in the Cement Industry in Southeast Europe - Trpkov, Stephanie Ekaette (Digital Repository of Theses, 2025)
This study investigates the adoption of green technologies within the cement industry in Southeast Europe (SEE), focusing on the strategic tensions and operational burdens confronting companies amid increasing demands for decarbonisation. Grounded in Institutional, Stakeholder, Dynamic Capabilities and Paradox Theories, the research analyses how cement companies, particularly in the EU member states in SEE (Bulgaria, Croatia, and Romania), manage institutional pressures, capital risk, and technology deployment in their transition toward industrial sustainability. Adopting a mixed-methods design, the study triangulates quantitative data on cement pricing, investment patterns, and emission indicators, with qualitative insights drawn from semi-structured interviews with corporate executives, industry experts, and policy stakeholders, as well as corporate sustainability disclosures. The findings reveal uneven policy enforcement, limited access to targeted green finance, and significant capability gaps in resolving strategic paradoxes and managing long-term technology integration. Companies face persistent trade-offs between short-term financial performance and long-term environmental obligations, within a risk-averse investment climate, amplified by reputational risk and stakeholder scrutiny. The analysis highlights the importance of dynamic capabilities in sensing regulatory shifts, seizing low-carbon investment opportunities, and reconfiguring core operations, as differentiating factors among companies. A comparative trend analysis of cement prices (2015–2025) illustrates the market-level effects of decarbonisation policies and underscores the varying pace of industrial adaptation across SEE. The study concludes with clear recommendations for strengthening managerial capacity to navigate strategic paradoxes, improving governance to curtail greenwashing, and aligning national frameworks with EU climate policy alongside corporate risk-reduction priorities. In the quest for a competitive and environmentally responsible industrial transformation, the findings contribute to a deeper understanding of how sustainability transitions unfold in energy intensive sectors within emerging European markets, offering nuanced insights for corporate leaders, policymakers, and researchers on sustainability as both a source of risk and opportunity. Keywords: Green technologies, cement industry, strategic tensions, sustainability paradoxes, decarbonisation, Southeast Europe.